Estudo dos aspectos ergonômicos nos colaboradores terceirizados da Ufersa – Campus Caraúbas - Oliveira, Suzy Aucênia de (Universidade Federal Rural do Semi-Árido, 2018)
Ergonomics provide man with a healthier and safer working environment, reducing physical and emotional exhaustion, making him more productive. The lack of knowledge on the subject implies in several negative factors such as the low productivity, remoteness and professional absence of the company and a series of complications for the health of the worker himself. Because it is an important tool that directly influences the productive capacity and the health of the worker, ergonomics is a norm of fundamental importance, which must be established and adapted according to the needs presented by the workers, thus helping in a better development of its activities. The present work begins with a bibliographical revision on Occupational Safety and NRs, with particular emphasis on NR 17, Regulatory Standard that normalizes Ergonomics. Through observations and application of a questionnaire to the employees of the sector, a study of the ergonomic aspects was carried out in the subcontracted employees of UFERSA - Campus Caraúbas. The result showed that the environment, the tools and equipment used well with the working conditions and the prevention of accidents are within the parameters required by NR 17. However, there is a deficit in relation to the promotion of the development of ergonomic activities within the Campus, with the aim of encouraging employees to carry out exercises directed at the activities they develop at work.
Monografia
Keywords: Ergonomia; Trabalhador; Prevenção de acidentes; Produtividade; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA